PENGARUH KELOMPOK TEMAN SEBAYA DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF SISWA SMPN 1 SIDOARJO - Tri Achmad Budi Susilo (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2021)
The focus of this study was to determine the effect of peer group variables and the use of social media on student consumptive behavior at SMPN 1 Sidoarjo. The type of research chosen is explanatory or explanatory research. The selected population coverage is 9 classes containing 297 students. The sampling method used was random or simple random sampling. The total sample selected was 30 students with the data collection step using a questionnaire. The questionnaire was then tested for validity, reliability, and residual normality. After the questionnaire passes the test, then the hypothesis test and statistical data analysis test is carried out. The results of the hypothesis test explain that there is an effect produced by peer group variables and the use of social media on students' consumptive behavior separately (partially) or simultaneously (simultaneously), while the results of the multiple coefficient of determination are known from the value of R Square (R2) of 0.826 or 82.6% (if a percentage) and the remaining 17.4% comes from other variables outside the study. If the peer group variable has a one-unit increase, the consumptive behavior variable will increase by 0.650. If the variable use of social media has increased by one unit, the consumer behavior variable has increased by 0.400 based on the results of multiple regression analysis.